Atlas of Craniocervical Junction and Cervical Spine Surgery - Boriani, Stefano; Presutti, Livio; Gasbarrini, Alessandro; Mattioli, Francesco (Springer International Publishing : Imprint: Springer, 2017)
This atlas documents current surgical approaches to the craniocervical junction and the cervical spine, providing step-by-step guidance on procedures and cervical spine stabilization techniques. Opening chapters present essential information on anatomy, depict pathologies with the aid of illustrative cases, describe the role of imaging techniques in patient evaluation, and discuss surgical instrumentation and patient positioning. The different techniques employed in this delicate anatomic region, including transnasal and transoral endoscopic approaches to the craniocervical junction and posterior and anterior approaches to the cervical spine, are then explained and illustrated with a view to providing the surgeon with a clear reference that can be used in the operating room. In addition, practical advice is offered on the treatment of potential complications, postoperative management, and rehabilitation. This book will be of value not only to neurosurgeons but also to orthopedists, ENT surgeons, neurologists, and physiatrists.
Keywords: Medicine.; Neurosurgery.; Orthopedics.; Otolaryngologic surgery.; Surgical oncology.; elektronické knihy; electronic books